Pharmacologic effects in vivo in brain by vector-mediated peptide drug delivery. - Bickel, U (1993)
Pharmacologic effects in brain caused by systemic administration of neuropeptides are prevented by poor transport of the peptide through the brain vascular endothelium, which comprises the blood-brain barrier in vivo. In the present study, successful application of a chimeric peptide approach to enhance drug delivery through the blood-brain barrier for the purpose of achieving a central nervous system pharmacologic effect is described. The chimeric peptide was formed by linkage of a potent vasoactive intestinal peptide (VIP) analogue, which had been monobiotinylated, to a drug transport vector. The vector consisted of a covalent conjugate of avidin and the OX26 monoclonal antibody to the transferrin receptor. Owing to the high concentration of transferrin receptors on brain capillary endothelia, OX26 targets brain and undergoes receptor-mediated transcytosis through the blood-brain barrier. Systemic infusion of low doses (12 micrograms/kg) of the VIP chimeric peptide in rats resulted in an in vivo central nervous system pharmacologic effect: a 65% increase in cerebral blood flow. Biotinylated VIP analogue without the brain transport vector was ineffective.